Novel GLI3 mutation in a Greek–Cypriot patient with Greig cephalopolysyndactyly syndrome. Issue 3 (July 2015) - Tanteles, George A.; Michaelidou, Sofia; Loukianou, Eleni; Christophidou-Anastasiadou, Violetta; Kleopa, Kleopas A.
<x xml:space="preserve">Abstract</x> Greig cephalopolysyndactyly syndrome (GCPS) is typically characterized by preaxial or mixed preaxial and postaxial polydactyly with or without syndactyly and craniofacial features including hypertelorism and macrocephaly. Although GLI3 shows considerable pleiotropy, it is the only gene known to cause this particular phenotype. We report on a patient with GCPS caused by a novel GLI3 mutation. In addition, the patient had asymmetry of the calf muscles, most likely secondary to chronic hypertrophic radiculopathy. The GLI3 mutation identified by targeted Sanger sequencing analysis in our patient is predicted to lead to premature termination of translation. This is the first report of a Cypriot patient with a GCPS because of a novel GLI3 mutation. The report provides additional evidence in support of the rich variability in phenotypic expression, the mutational heterogeneity and ethnic diversity associated with this rare condition.